The Implementation of E-Wallet on the Efficiency of Financial Management of Mataram University Students - Fajrin, Muhammad Fadhly; Pusparini, Herlina (Indonesian Journal of Banking and Financial Technology, 2024)
This study aims to examine the effect of e-wallet implementation on the efficiency of financial management of Mataram University students. This study uses associative research with a quantitative approach. Using the Slovin formula from a population of 35,271 which resulted in 395 students selected as research samples. Data collection techniques online via google form. Research data analysis was carried out using SmartPLS 3.0. The results showed that the implementation of e-wallets had a significant effect on the efficiency of financial management of Mataram University students. This study suggests that e-wallet implementation is carried out wisely in order to have a good impact on financial management behavior, especially among students.